Charles Cohen: capstone - Cohen, Charles, artist (Colorado State University. Libraries, 2024)
The artist's statement: I'm Charlie Cohen, a graphic designer from Colorado State University with over 4 years of professional experience. I am captivated by finding new ways to solve problems, prioritizing functionality and experimentation in my designs. Design isn't just a job for me; it's how I interpret the world. Seeking junior positions in graphic design and motion graphics.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design